Is the 28-day rule safe for use in abdominal radiography? - Moey, Soo Foon; Che Mohamed, Norfariha; Saidin, Nursyahirah (Mashhad University of Medical Sciences, 2020)
Introduction: The 28-day rule is utilized as a precautionary measure for irradiating the fetus at an early stage of conception for abdominal and pelvic radiography. There is a probability of the women being pregnant if the 28-day rule is applied for this examination and thus irradiating the conceptus. It is difficult to convince people that low radiation doses during early pregnancy will not cause any harm to the conceptus. As such this study was to ascertain whether the 28-day rule can be used safely for abdominal radiography in women of reproductive age. Materials and Methods: The experimental study was conducted at the Radiography Laboratory, International Islamic University Malaysia, Kuantan using an anthropomorphic PBU-50 phantom. The entrance surface dose (ESD), organ dose and effective dose (ED) were estimated using CALDose_X 5.0 software, based on the exposure parameters and tube output of the x-ray unit. Results: The mean ESD for AP abdominal radiographic examination of 3.162 mGy is within that recommended by radiation protection regulatory bodies. Additionally, the mean organ dose of 0.468 mGy is lower than the threshold value of 100 mSv for the “all-or-none” phenomenon to happen. Further, the mean ED of 0.73 mSv is within the recommendation of the International Atomic Energy Agency (IAEA) and the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). Conclusion: This study indicated that the 28-day rule is safe to be used for abdominal radiography for a woman of reproductive age.